Proteomic analysis of infiltrating neutrophils from rheumatoid arthritis synovial fluid and their contribution to protein carbamylation - Chen, Xueting; Du, Rong; Wang, Pan; Qiu, WenLin; Chen, Lu; Wan, Jian; Qiu, Hui; Xiong, Li; Nandakumar, Kutty Selva; Holmdahl, Rikard; Geng, Hui (Frontiers in Immunology, 2025)
IntroductionCarbamylated proteins and dysregulated neutrophils are implicated in rheumatoid arthritis (RA) pathogenesis. Herein, we characterized the neutrophils present in RA synovial fluid (SF) using proteomic techniques and evaluated their contribution to protein carbamylation.MethodsRA-SF neutrophil proteomic profile and SF proteome signature were investigated using high-resolution mass spectrometry. Carbamylated proteins and the degree of protein carbamylation were evaluated by mass spectrometric analysis. ELISA and chemiluminescence kits were used to examine myeloperoxidase (MPO) activity, and hydrogen peroxide (H2O2) generation.ResultsSF neutrophils exhibited a shift in proteomic cargo with up-regulated proteins involved in defense responses, neutrophil degranulation, and reactive oxygen species metabolic processes, while proteins down-regulated were associated with megakaryocyte differentiation, leukocyte migration, and integrin-mediated signaling pathway. Elevated levels of neutrophil-derived proteins were detected in RA-SF. In addition, we specifically identified many carbamylated proteins and observed an increased frequency of protein carbamylation in RA-SF samples. Functionally, neutrophils from RA-SF showed a significantly increased level of MPO release and HH2O2 generation. Moreover, MPO activity was higher in RA-SF than in autologous blood samples, which correlated well with the degree of protein carbamylation in RA-SF.DiscussionSynovial neutrophils were found to be activated and increased releasing protein cargo, including MPO and ROS, into the synovial fluid. Presence of many carbamylated proteins in RA-SF and an increased MPO activity showed a strong correlation to the degree of protein carbamylation, suggesting neutrophil-derived MPO in promoting generation of aberrantly carbamylated proteins.